Dengue virus entry and trafficking: Perspectives as antiviral target for prevention and therapy - Castilla, Viviana (2015)
Dengue virus (DENV) is the etiological agent of the most important human viral infection transmitted by mosquitoes in the world. In spite of the serious health threat that dengue represents, at present there are no vaccine or antiviral agents available and treatment of patients consists of supportive therapy. This review will focus on the process of DENV entry into the host cell as a potential target for antiviral therapy. The recent advances in the knowledge of viral and cellular molecules and mechanisms involved in binding, internalization and trafficking of DENV into the host cell until virion uncoating are discussed, together with an overview of the strategies and compounds evaluated for development of antiviral agents targeted to DENV entry.